2021
DOI: 10.3390/molecules26071913
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Amyloid Typing by Proteomics: Performance Evaluation and Data Sharing between Two Centres

Abstract: Amyloidosis is a relatively rare human disease caused by the deposition of abnormal protein fibres in the extracellular space of various tissues, impairing their normal function. Proteomic analysis of patients’ biopsies, developed by Dogan and colleagues at the Mayo Clinic, has become crucial for clinical diagnosis and for identifying the amyloid type. Currently, the proteomic approach is routinely used at National Amyloidosis Centre (NAC, London, UK) and Istituto di Tecnologie Biomediche-Consiglio Nazionale d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In our study, the high amount of bovine serum gave an interference that can impair the use of the typical protein validation methodologies such as ELISA and Western Blot, considering also their limitations in quantification, antibodies availability and the number of markers to be investigated. MS-based validation methods, such as Multi-Reaction Monitoring (MRM) [ 68 ] or the analysis of a second cohort of samples [ 69 ] represent good alternatives, and it would be of great importance to validate proteins in the context of proteomic analysis, although they are time-consuming and require a high number of samples. In the future, it will be necessary to perform other studies on samples, possibly without bovine serum medium, to confirm the reported data with validation methods (especially MS-based) and to increase the knowledge about boron and neutron effects, with the aim to apply this approach also in vivo, on both treated animal models and patients.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the high amount of bovine serum gave an interference that can impair the use of the typical protein validation methodologies such as ELISA and Western Blot, considering also their limitations in quantification, antibodies availability and the number of markers to be investigated. MS-based validation methods, such as Multi-Reaction Monitoring (MRM) [ 68 ] or the analysis of a second cohort of samples [ 69 ] represent good alternatives, and it would be of great importance to validate proteins in the context of proteomic analysis, although they are time-consuming and require a high number of samples. In the future, it will be necessary to perform other studies on samples, possibly without bovine serum medium, to confirm the reported data with validation methods (especially MS-based) and to increase the knowledge about boron and neutron effects, with the aim to apply this approach also in vivo, on both treated animal models and patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mass spectrometry for the determination of amyloid type was pioneered by researchers at the Mayo Clinic and is now an established method in many laboratories (32,33). The technique is most commonly based on formalin-fixed and paraffinembedded materials, from which amyloid is dissected with laser dissection microscopy (LDM).…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…The proteomic analysis of ex vivo tissues has provided relevant information in this respect [ 14 , 18 , 20 , 57 , 80 , 88 ]. Besides the main fibrillar precursor, other blood-borne proteins and specific tissue proteins (so-called “amyloid protein signature”, or “amyloid-associated proteins”) are commonly associated with fibrils, regardless of the amyloidosis type [ 21 , 22 , 57 , 88 , 89 ]. In addition, other molecules, such as glycosaminoglycans and lipids, co-localize with aggregates [ 3 , 90 ].…”
Section: The Al Amyloid Proteome: Disease Typing Characterization Of Deposited Lc Proteoforms and The Amyloid Environmentmentioning
confidence: 99%
“…Proteins typically found in amyloid deposits include, among others, serum amyloid P (SAP), apolipoprotein E (ApoE), apolipoprotein AIV (ApoAIV) [ 22 ], vitronectin (VTN) [ 92 ], complement and clusterin [ 93 ]. The fact that these proteins are “universal” amyloid components has led to suggest that the concomitant presence of several of these species in the proteome map of a tissue could be used as an “amyloid proteome signature”, useful for diagnostic purposes [ 22 , 88 , 89 ]. In fact, identification of at least two among ApoE, SAP and ApoAIV was proposed as a mean to discriminate between amyloid-positive and amyloid-negative samples, and is often used as a surrogate to indicate that the sample contains amyloid fibrils.…”
Section: The Al Amyloid Proteome: Disease Typing Characterization Of Deposited Lc Proteoforms and The Amyloid Environmentmentioning
confidence: 99%